A systematic review of non-drug interventions to prevent and treat anxiety in people with aphasia after stroke. Issue 18 (28th August 2022) - Ryan, Brooke J.; Clunne, Stephanie M.; Baker, Caroline J.; Shiggins, Ciara; Rose, Miranda L.; Kneebone, Ian I.
Abstract: Purpose: To investigate the effectiveness of non-drug interventions for people with aphasia in the prevention and/or treatment of anxiety post-stroke as either a primary or secondary outcome. Materials and Methods: A systematic search of Medline, CINAHL, PsycINFO and Cochrane Library up to March 2021 was carried out. Studies of stroke populations were included if people with aphasia represented 25% or more of the enrolled participants. Quality of the evidence was assessed. A narrative synthesis of results is presented. The PROSPERO record ID for this study is 106451. Results: Ten studies were included: five randomised controlled trials (RCTs), a single case experimental design, and four pre-post studies. The quality of the RCT trials was at least adequate but none demonstrated a benefit to anxiety outcomes. Those studies that reported benefit were of lower-level evidence with respect to National Health and Medical Research Classifications. No studies were found that evaluated the prevention of anxiety after stroke for people with aphasia. Conclusion: Definitive conclusions about the effectiveness of non-drug interventions for the prevention and/or treatment of anxiety in people with aphasia post-stroke cannot be made. Interventions that may show promise for those with aphasia and symptoms of anxiety include mindfulness meditation, modified cognitive behaviour therapy, unilateral nostril breathing, and the "Enhance Psychological Coping after Stroke" programme. Further high-quality research with better reporting of the inclusion of participants with aphasia and their specific sub-group results are required. Implications for Rehabilitation: It is important for rehabilitation professionals to consider prevention of anxiety post-stroke as well as treatment. Mindfulness meditation, modified cognitive behavioural therapy, unilateral nostril breathing, and the and the "Enhance Psychological Coping after Stroke" programme may be of benefit to people with aphasia post-stroke. Adapting intervention protocols to be more communicatively accessible and training health professionals in supported communication may help people with aphasia engage in psychological therapies.